Ensuring the economic security of the country in the new geopolitical realities - Yu. N. Kafiyatullina; G. P. Kharchilava (Вестник университета)
The issue of ensuring Russia’s economic security is an important and priority task, especially in the tightening conditions of the consolidated sanctions policy of the European Union countries and the United States. The process of developing measures that allow Russian economy to develop sustainably and effectively counter the growing geopolitical threats is complex and requires a comprehensive and honest assessment, including the import dependence degree of business, the degree and level of involvement in global supply chains, the development level of domestic production, etc. For each assessment area, indicators should be identified that have a preventive nature and make it possible to detect a growing potential threat. In the research theoretical provisions on economic security are considered; existing threats to economic security in geopolitical realities are formulated; indicators presented by the Federal State Statistics Service are identified that allow assessing the threat degree; directions for ensuring economic security are developed.